Geomorphological classification and landscape evolution in a sector of Sierras Australes, Buenos Aires Province - Pereyra, F.X. (1996)
The main geomorphological features of a sector of Sierras Australes (Buenos Aires province) are described. Fluvial processes (mainly formation of alluvial fans), mass wasting (creep and debrisflows) and wind action (deflation and acumulation) are responsible for the configuration of the landscape of the region. At least three alluvial acumulation events and equal number of loess deposition were recognized for the late Cenozoic times. The development of a planation surface of pre-Cenozoic age, and developed in Palaeozoic rocks, is postulated. This surface and the piedmont acumulations were affected by erosional events related to tectonic, climatic and eustatic events (Andean Orogeny and glaciations). Six major geomorphological units are recognized. Today the pedogenetic processes predominate whereas morphodynamic ones are low.